Legitimising Magic
1 online resource (212 pages)
Keywords: As magic is a powerful means to influence the natural world and human beings, and is deeply connected to the divine sphere, persons using it are in constant need to justify its use. The ambivalence of magic to serve both well-wishing and ill-wishing aims puts the practitioners ever at risk. This volume illuminates the strategies adopted to legitimise the practice of magic and analyses how these justifications are phrased and formulated in cuneiform texts, thereby revealing the underlying principles and unexplained axioms of using magic in the Ancient Near East.